The Family 500+ benefit and changes in female employment in Poland - Krzysztof Bartosik (Central European Economic Journal (CEEJ), 2023)
This paper investigates the relationship between the implementation of the Family 500+ benefit, changes in female employment and female economic inactivity. The analysis is based on macro data and is focused on the years 2016-2019. To examine the relationship, this study uses decomposition of the employment-to-population ratio change into labour supply and unemployment components, analysis of changes in the structure of nonparticipants and the shift-share method. Considering that the reaction to the child benefit may differ across age groups, this study found that since the introduction of the Family 500+ benefit, the employment-to-population ratio for women aged 25-39 (the most likely age group to be raising children and therefore to receive the benefit) stagnated, their labour force participation rate decreased and the percentage of nonparticipants due to family and household responsibilities increased.
Keywords: E24; J21; J16; H24; 330; female employment; child benefits; family policy; employment-to-population ratio